1992
DOI: 10.1021/j100193a001
|View full text |Cite
|
Sign up to set email alerts
|

Anionic polymerization in the gas-phase cluster of 2-chloroacrylonitrile

Abstract: Intracluster reactions in the gas-phase cluster of 2-chloroacrylonitrile (CAN) following the collisional electron transfer from a high-Rydberg Kr atom (Kr**) were investigated by mass spectrometry. The cluster anions (CAN); with n 2 1 and [(CAN),-n'HCll-with 2 I n I 4 and n ' l 1 were observed. The formation of [(CAN),-n'HCI]-indicates that intracluster anionic polymerization takes place and that excess energy associated with the polymerization is used for eliminating HCl molecules from the corresponding nasce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 6 publications
3
28
0
Order By: Relevance
“…Meanwhile, considerable effort has been devoted to the investigation of these ion−molecule reactions in the cluster regime as well. This has been prompted by the recognition that interrogating clusters provides a way of studying the energetics and dynamics of intermediate states of matter as cluster systems evolve from the gas toward the condensed state .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, considerable effort has been devoted to the investigation of these ion−molecule reactions in the cluster regime as well. This has been prompted by the recognition that interrogating clusters provides a way of studying the energetics and dynamics of intermediate states of matter as cluster systems evolve from the gas toward the condensed state .…”
Section: Introductionmentioning
confidence: 99%
“…Low-energy electron attachment to neutral clusters of 2-chloroacrylonitrile (CAN) creates a complex distribution of anions consistent with the occurrence of an intracluster polymerization reaction. 1 Previously, we proposed that the key to understanding the polymerization mechanism lay in the structure of the CANmonomer anion. We had investigated the ion using photofragmentation techniques and observed CANfragmenting at 2.33 eV, yielding primarily Clwith a small amount of [H2C=CCN]-, indicating that CANhas a dissociative low-lying electronic state.2 This was slightly surprising since similar molecules such as acrylonitrile (H2C=CHCN) have low electron affinities (< 1 eV),3 so that electron detachment would be expected to occur well below such an absorption band.…”
Section: Introductionmentioning
confidence: 99%
“…28 A similar anionic polymerization and sequential elimination of HC1 have been observed in electron attachment onto clusters of 2-chloroacrylonitrile (CAN). 29 In a photodissociation study on dimeric anions, [(CAN)2 -mHCl]*-(m = 0-2), the elimination of one HC1 molecule is the dominant channel. 30 In the electron attachment to clusters of methyl acrylate (MA), the intensity of (M A) 5-is enhanced at a higher stagnation pressure and explained by chemical-bond formation in the cluster anion; i.e., intracluster anionic polymerization occurs in (MAV-.31 These mass spectroscopic studies on the intracluster ionic polymerization reactions have suggested that (i) the formation of stable ions leads to the termination of the chain-propagation sequence of the polymerization and (ii) the evaporation of unreacted monomers and/or the elimination of neutral species are the main relaxation pathways for producing the nascent polymeric ions in the gas phase.…”
mentioning
confidence: 99%